Electrospun Zein Fibers Incorporating Poly(glycerol sebacate) for Soft Tissue Engineering - Vogt, Lena (Nanomaterials (Basel), 2018)
For biomedical applications such as soft tissue engineering, plant proteins are becoming increasingly attractive. Zein, a class of prolamine proteins found in corn, offers excellent properties for application in the human body, but has inferior mechanical properties and lacks aqueous stability. In this study, electrospun scaffolds from neat zein and zein blended with prepolymer and mildly cross-linked poly(glycerol sebacate) (PGS) were fabricated. Less toxic solvents like acetic acid and ethanol were used. The morphological, physiochemical and degradation properties of the as-spun fiber mats were determined. Neat zein and zein-PGS fiber mats with high zein concentration (24 wt % and 27 wt %) showed defect-free microstructures. The average fiber diameter decreased with increasing PGS amount from 0.7 ± 0.2 µm to 0.09 ± 0.03 µm. The addition of PGS to zein resulted in a seven-fold increase in ultimate tensile strength and a four-fold increase in failure strain, whereas the Young’s Modulus did not change significantly. Degradation tests in phosphate buffered saline revealed the morphological instability of zein containing fiber mats in contact with aqueous media. Therefore, the fibers were in situ cross-linked with N-(3-Dimethylaminopropyl)-N′-ethylcarbodiimide (EDC)/N-Hydroxysuccinimide (NHS), which led to improved morphological stability in aqueous environment. The novel fibers have suitable properties for application in soft tissue engineering.